Modeling of diode in FDTD simulation of printed circuit board - Kung, F.; Chuah, H. T. (Taylor & Francis Group, 2002)
Finite-Difference Time-Domain (FDTD) method has evolved into a powerful tool to model electromagnetic wave propagation in a printed circuit board environment [1-7]. A simple, efficient and systematic approximate method to incorporate nonlinear diode is presented in this paper. This method applies Taylor expansion on the nonlinear diode equation, which result in one step explicit finite difference scheme for the electromagnetic fields in the vicinity of the diode. Simulation examples axe performed. The result compares well with FDTD diode model using iterative solution approach and SPICE simulation.